An Investigation of the Effects of Emitter Pre-Deposition Temperature in Double-Diffued Polysilicon Emitter Bipolar Transistors - E.F Chor; C.P Chen; L.S Tan (Universitas Gadjah Mada, 1988)
An Investigation of the Effects of Emitter Pre-Deposition Temperature in Double-Diffued Polysilicon Emitter Bipolar Transistors